2020
DOI: 10.1038/s41467-020-18919-2
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 gene amplification promotes expansion of Cancer Associated Fibroblast populations in human skin

Abstract: Cancer associated fibroblasts (CAFs) are a key component of the tumor microenvironment. Genomic alterations in these cells remain a point of contention. We report that CAFs from skin squamous cell carcinomas (SCCs) display chromosomal alterations, with heterogeneous NOTCH1 gene amplification and overexpression that also occur, to a lesser extent, in dermal fibroblasts of apparently unaffected skin. The fraction of the latter cells harboring NOTCH1 amplification is expanded by chronic UVA exposure, to which CAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
(107 reference statements)
1
23
0
1
Order By: Relevance
“…To determine the modalities of cell death, early-stage cell apoptosis (green), late-stage cell apoptosis (green and red) and necrosis (red) were simultaneously monitored using the Apoptosis/Necrosis Assay Kit [ 31 ]. As shown in Figure 1 F,G, SLC17A9 deficiency induced both early-stage and late-stage apoptosis, but not necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the modalities of cell death, early-stage cell apoptosis (green), late-stage cell apoptosis (green and red) and necrosis (red) were simultaneously monitored using the Apoptosis/Necrosis Assay Kit [ 31 ]. As shown in Figure 1 F,G, SLC17A9 deficiency induced both early-stage and late-stage apoptosis, but not necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…By acquiring cancer cell DNA through phagocytosis, TAMs may gain tumorigenic functions that enhance tumor invasion and metastasis [ 318 ]. Recent studies found that CAFs isolated from premalignant and malignant skin squamous cell carcinoma were characterized by chromosomal abnormalities and genomic instability [ 320 , 321 ]. Katarkar et al showed that CAFs with karyotype aberrations that amplified NOTCH1 suppressed DNA damage-induced ATM signaling and cell cycle arrest in response to UV irradiation, promoting their survival over other CAFs [ 321 ].…”
Section: The Role Of Aneuploidy and Polyploidy In Tumor Niche Constructionmentioning
confidence: 99%
“…Recent studies found that CAFs isolated from premalignant and malignant skin squamous cell carcinoma were characterized by chromosomal abnormalities and genomic instability [ 320 , 321 ]. Katarkar et al showed that CAFs with karyotype aberrations that amplified NOTCH1 suppressed DNA damage-induced ATM signaling and cell cycle arrest in response to UV irradiation, promoting their survival over other CAFs [ 321 ]. Therefore, stromal cells with favorable genomic changes can indeed undergo positive selection during tumor progression, and the identification of such events could unlock new stroma-focused anti-cancer intervention strategies.…”
Section: The Role Of Aneuploidy and Polyploidy In Tumor Niche Constructionmentioning
confidence: 99%
“…To provide a possible rationale and propose a mechanism which explains the temporal differences in the response to TGFβ blockade in the mCAFs, we hypothesized that genes possibly affected by copy number variations (CNVs) within the myCAF population may provide resistance cues to TGFβ inhibition. While considered a hallmark of the cancer compartment and not confirmed in all studies , several reports have suggested cancer associated fibroblasts to harbor chromosomal aberrations and structural genomic variants in the form of chromosomal amplifications and losses promoting cancer cell invasion and tumor growth (31)(32)(33). Genomic instability including amplification of gene loci is a well-known mechanism of resistance to targeted therapy in cancer cells (34).…”
Section: Mycafs Harbor Copy Number Variations (Cnvs) Affecting Genes Associated With Caf Activationmentioning
confidence: 99%